Effect of alloying elements on fracture behavior of Fe-18Ni-2Ti-(8Co) alloys - Heo, NH; Na, JG (KOREAN INST METALS MATERIALS, 1997)
Effect of alloying elements on fracture behavior of Fe-18Ni-2Ti-(8Co) alloys has been investigated in the light of grain boundary segregation of alloying elements. During isothermal aging at 540 degrees C, hardness level in the cobalt-bearing alloy was higher than that in the cobalt-free alloy, which is attributed to the solid solution hardening of cobalt, and the bigger hardness difference after overaging was due to the relatively fine precipitates in the cobalt-bearing alloy. The grain boundary segregation behavior of the elements was similar in two alloys, regardless of the cobalt addition. In two alloys, the fracture behavior before and after the maximum tensile strength is mainly governed by two factors: titanium at the grain boundaries and overaging. Up to the aging time corresponding to the maximum tensile strength, the intergranular fracture strength was roughly inversely proportional to the titanium level at the grain boundaries, and after the time the tensile strength decreased with restoring ductility. Nickel or cobalt was not effective on the grain boundary strengthening of the iron-based alloys.
Keywords: BRITTLE-DUCTILE TRANSITION; GRAIN-BOUNDARY SEGREGATION; NONEQUILIBRIUM SEGREGATION; MN; EMBRITTLEMENT; ADSORPTION